Application of CFD-DEM to investigate seepage characteristics of landslide dam materials. (September 2018) - Shi, Zhen-Ming; Zheng, Hong-Chao; Yu, Song-Bo; Peng, Ming; Jiang, Tao
Abstract: A coupled computational fluid dynamics and discrete element method was presented to quantitatively investigate the seepage characteristics of fine and coarse materials relevant to landslide dam. The numerical model was verified by comparing the calculated seepage parameters, critical hydraulic gradient and failure mode with the corresponding tests. The microcosmic mechanisms of the seepage failure were studied by considering seepage field, force chain, and particle trajectory. The failure mode of fine-grained soils was flowing soil because the effective stress was close to zero. However, for coarse-grained soils, the failure mode was piping that resulted from the presence of some effective stress.